Genetic Anticipation - Qurrata’yuni Pratiwi (Rifa'Institute, 2022)
Several genetic conditions show the phenomenon of genetic anticipation. Anticipation is a phenomenon where genetic disorders are passed on to the next generation genetic disorders become apparent at an earlier age with each generation. In most cases, an increase in the severity of symptoms is also noted. General anticipation occurs in trinucleotide repeat disorders, such as Huntington's disease and Myotonic dystrophy, where does it occur? dynamic mutations in DNA. All of these diseases have neurological symptoms